A Multimedia Tool to Deliver Professional Development of Vocabulary Instruction. Issue 1 (March 2015) - Ely, Emily; Pullen, Paige C.; Kennedy, Michael J.; Williams, Mira Cole
Supporting teachers' implementation of evidence-based vocabulary practices with fidelity during instruction is critical. In this study, researchers investigated a multimedia-based intervention that integrates a modeling video and a Content Acquisition Podcast (i.e., video plus CAP) to teach elementary teachers how to implement a vocabulary intervention to students performing below grade level. The video plus CAP tool was created based on theories of cognitive learning. Researchers observed teachers during a four-week span following professional development using this intervention. Results demonstrated that teachers consistently increased their use of practices associated with an evidence-based vocabulary intervention. The video plus CAP tool has promising implications for teacher professional development as a way of bridging the research to practice gap.